Di Bawah Spirit Liberal-Institusionalisme: Kajian Komparatif Gagasan Dynamic Equilibrium dan ASEAN Outlook on the Indo-Pacific - Ardianti, Dinar Elly; Rosyidin, Mohamad; Alfian, Muhammad Faizal (Indonesian Perspective, 2023)
This article aims to compare two Indonesia’s foreign policy ideas, namely, dynamic equilibrium and the ASEAN Outlook on the Indo-Pacific (AOIP). It treats both ideas as an analytical tool instead of propositions to be tested against empirical evidence. Using liberal-institutionalism approach, this article argues that despite both ideas applies in the Indo-Pacific region, both have different characteristics. While dynamic equilibrium can be regarded as a foreign policy doctrine which only proposes the basic principles of interstate relations, AOIP is a cooperative framework which becomes policy guidance for countries in the region. However, both ideas conforms liberal-institutionalism premises that international regimes matter because it provides set of rules for cooperation rather than rivalry, recover ASEAN’s role as a key actor in the region, promote dialogue in dispute settlement, and gain economic development.